Effect of Nanomaterial on the Properties of Ultra High Performance Concrete - Nada Mahdi Fawzi Aljalawi (Iraqi Journal of Industrial Research)
In recent years, there is a great interest in many countries to use the limestone powder in produce concrete by the replacing it as a proportion of cement weight able to improving the properties of the concrete as well as this type of powder lead to the reducing concrete cost and the CO2 emissions through the process of cement industry. This study examined of the effect of the limestone powder indifferent proportion (5, 10, 15, and 20) % replaced by the weight of cement on the properties of Ultra High Performance Concrete). Where it included five tests consisted of workability of fresh concrete (slump test method), compressive strength, tensile strength, water absorption, and density. The Results show the possibility of replacing 15% of the cement weight with limestone powder lead to improving of concrete strength but negative effects on the properties observed as the amount of limestone powder exceeds this ratio.